Modified Mohs Micrographic Surgery and Rotational Flap in The Treatment of Basal Cell Carcinoma - Idris, Irma Suryani; Anwar, Anis Irawan; Purnamasari, A. Bida (Jurnal Biologi Tropis, 2024)
A malignant tumor that starts in the basal layer of the epidermis is called basal cell carcinoma (BCC). The most prevalent type of skin cancer, BCC, usually appears on the face of middle-aged or older individuals. They originate from the epidermis' basal keratinocytes, are locally invasive, and hardly ever spread. One of cases BCC was reported in a 43 years old man at dermato-venereology department hospital in Makassar. Diagnosis was established based on history taking, clinical features, histopathology examination through Modified Mohs Micrographic Surgery Technique (MMS). The management for this patient was rotation flap technique and gave a good improvement.